IMPLEMENTASI MODEL CONTEXTUAL TEACHING AND LEARNING DALAM PEMBELAJARAN FIQIH DI MTS SALAFIYAH SYAFI’IYAH SEBLAK - El-Fitri, Rizky Wahyu; Ilahiyah, Iva Inayatul (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2022)
Abstract: The Contextual Teaching and Learning model is a learning concept that encourages teachers to make connections between the material being taught and students' real world situations. And also encourage students to make connections between the knowledge they have and its application in their own lives. The focus of the problem in this research are: (1) How is the Implementation of Contextual Teaching and Learning Model in Fiqh learning at MTs Salafiyah Syafi'iyah Seblak?, (2) What are the inhibiting and supporting faktors for Implementation of Contextual Teaching and Learning Model in Fiqh learning at MTs Salafiyah Shafi'iyah Seblak? In this thesis research uses field qualitative research, while the approach uses case studies, data collection techniques use observation, interviews, and documentation. (1) the implementation of the Contextual Teaching and Learning Model in learning fiqh at MTs Salafiyah Syafi'iyah Seblak, learning that is implemented with what is in nature is then used in learning as in class 1 chapter Thaharahanak was told to look for tools that can be used for purification. then the teacher also assigned his students to bring various kinds of water such as degan water, colored water and so on so that they could distinguish between types of water that were clean, muthahir, pure water, ghoiru muthahir, and muthlak water. to be eaten with halal food in grade 3 about hiwalah or turning debt so that children bring tools or necessities in that chapter will be evaluated later. (2) The inhibiting and supporting faktors for implementing the Contextual Teaching and Learning Model in learning fiqh at MTs Salafiyah Syafi'iyah Seblak there are several supporting faktors such as the availability of facilities or infrastructure, for example, mosques and projectors. The inhibiting faktor at MTs Salafiyah Safiiyah Seblak takes turns using school facilities and sometimes errors occur in the media used in learning, children pay less attention when explained, do not focus when learning in class.